Sanjeevani: A Centralized Data Repository to Search Real-Time Emergency Medical Supplies - Tadvi, Shabana; Kagalwala, Husain; Amrelia, Mustufa; Kagdiwala, Zenab (International Journal of Computer Sciences and Engineering, 2018)
These days, with a bustling way of life individuals of all age aggregate battle with well-being related issues. Also searching for suitable blood groups and medicines in an emergency situation is strenuous task for family members which requires most extreme time and human exertion and now and then turns out to be exceptionally important that may cost the life of the patient. In this manner, HealthCare has turned into a required need of each family. To solve health related problem, we propose a Web based platform to ease the process of finding suitable blood groups from nearby Blood Banks in the area. Likewise, the application discovers conventional and its substitute drug from Medicine Shops accessible in the region utilizing Real time Location of the particular client/s through GPS. Subsequently, it reduces paperwork on daily basis of hospital blood banks by maintaining a database that will work in real-time for blood record maintenance.